PENILAIAN ASET TETAP BERWUJUD PADA CV FRANCO DI KOTA AMBON - Nova Angelin Kailuhu; Maxmilian Ernst Mauwa; Elisabeth Riupassa (P3M Politeknik Negeri Ambon, 2026)
Fixed assets require periodic revaluation to ensure that their carrying amounts accurately reflect actual asset values. Proper valuation of fixed assets is essential for presenting an accurate representation of a company’s tangible assets in the balance sheet and constitutes a fundamental principle of accounting practice, particularly in supporting the reliability and relevance of financial information. However, CV Franco has not performed depreciation calculations on its fixed assets, resulting in reported asset values that do not reflect their actual book value and potentially affecting the accuracy of financial statements. This study was conducted at CV Franco in Passo, Ambon, with a focus on fixed assets in the form of excavators and dump trucks. The research employed a descriptive quantitative approach using primary data derived from the company’s fixed asset records. Data analysis was carried out using the straight-line depreciation method. The findings indicate that the total value of fixed assets amounts to IDR 3,054,360,000.00, with an acquisition cost of IDR 3,660,000,000.00 and accumulated depreciation of IDR 605,640,000.00. Keywords: Fixed Asset Assessment, Acquisition Cost, Accumulated Depreciation